Bamboo blade. The complete series [videorecording (DVD)] - Saitō, Hisashi; Totsuka, Masahiro (Funimation Entertainment, 2009)
"It didn't take long for pint-sized Tamaki's lightning reflexes to catch the eye of starving Kendo instructor Toraji. This second-rate sensei is an embarrassment to the sport, and his Kendo club is running out of members. His only hope for redemption -- and a full belly -- is to get Tamaki to sign-on as his star pupil. Unfortunately this sword-wielding prodigy is a serious anime addict, so it'll be a challenge to get her to step away from the television and into the dojo. But once she feels like a part of the team, Tamaki will put down the remote and pick up her sword as Toraji turns his girls into a fearsome sisterhood of the bamboo blade!"--Container.